Amphiphilic photosensitizer polymer as a nanocarrier of cytotoxic molecule for carrier‐free combination therapy. Issue 1 (9th February 2023) - Xin, Jingqi; Deng, Caiting; Zheng, Meichen; An, Feifei
Abstract: Various nanocarriers have been explored to deliver drugs for combination therapy. However, most nanocarriers are composed of inert materials without contribution for improving the cancer therapeutic effect. Herein, a hydrophobic photosensitizer is conjugated to poly (ethylene glycol) to form an amphiphilic polymer, which further self‐assembles into nanomicelle. The generated nanomicelle can act as a nanocarrier to encapsulate a cytotoxic molecule, IR‐775, for combination therapy. The yielded nanodrug is totally composed of pharmacologically active ingredients to avoid any possible toxicity resulted from carrier materials. The nanodrug performs enhanced therapeutic effect compared with any monotherapy and exhibits negligible hemolysis, indicating good biocompatibility for further in vivo applications. Abstract : Amphiphilic PhA‐PEG5000 polymer can self‐assemble into nanoparticles to perform as not only a photosensitizer but also a drug carrier to deliver chemotherapeutic drugs, achieving photo‐chemo combination therapy. The design of the PhA‐PEG5000 is the key‐point to significantly improve the total drug loading of the nanomedicine for enhanced combination therapy.